Lithium ion battery and electric appliance thereof
By introducing differentized price AB ions in the positive electrode material of lithium ion batteries, and adding BF3 and LIQPROSFT to the electrolyte to form complexes, solve the poor stability of the positive interface in the lithium ion battery in low temperature environments, poor SEI membrane stability, and the stability of the SEI membrane, and The problem of large negative impedance has significantly improved the battery's low temperature discharge capacity and large -rate charging performance of normal temperature.
Patent Information
- Application Number
- CN202411266478.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-10
AI Technical Summary
Lithium-ion batteries have poor positive electrode interface stability, poor SEI film stability and large negative electrode impedance in low-temperature environments, resulting in poor performance of batteries in high-rate charging and discharging performance and low-temperature discharge capacity.
The main material with the general chemical formula LiaMOb is used to form an NP structure similar to a semiconductor diode by controlling the radial distribution of AB ions with different valences in the cathode material. At the same time, BF3 and LiqPrOsFt are added to the electrolyte. BF3 and LiqPrOsFt form a complex to improve the dissociation ability of SEI and reduce the negative electrode impedance.
By adjusting the structure of the cathode material and the composition of the electrolyte, the interface stability, thermal stability and electrochemical performance of the lithium-ion battery are improved, and the low-temperature discharge capacity and normal temperature high-rate charging performance of the battery are enhanced.
Smart Images

Figure BDA0005037281850000101 
Figure BDA0005037281850000111 
Figure BDA0005037281850000121
Abstract
Description
Technical Field
[0001] The present invention relates to the field of secondary batteries, and in particular to a lithium ion battery and an electrical appliance thereof. Background Art
[0002] Lithium-ion batteries play a vital role in many applications, especially in mobile communications, electric vehicles and large-scale energy storage systems. However, with the advancement of technology and the continuous growth of market demand, the performance requirements for lithium-ion batteries are also increasing, especially in terms of high-rate charge and discharge performance. When charging at high rates at room temperature, lithium-ion batteries face a series of technical challenges.
[0003] First, the speed at which lithium ions migrate between electrodes becomes a limiting factor. When the battery is charged at a high rate, the rapid migration of lithium ions leads to a significant increase in the lithium ion concentration gradient between the electrodes. Especially at the negative electrode, the limitation of the lithium ion embedding speed leads to the formation of lithium dendrites. Lithium dendrites are a microstructure of metallic lithium, and their growth not only reduces the cycle stability and service life of the battery, but also greatly increases the risk of short circuit and thermal runaway, seriously threatening the safety of the battery.
[0004] Secondly, the volume effect and phase change problems of electrode materials during the process of lithium insertion and extraction are also key factors. The positive and negative electrode materials will expand and shrink in volume during the charging and discharging process. Long-term cycling will cause the material structure to break, affecting the smooth migration of lithium ions. In addition, some positive electrode materials are accompanied by phase transfer changes during the charging and discharging process, which further increases the instability of the material structure. These effects not only affect the energy density and cycle life of the battery, but may also lead to the destruction of the solid electrolyte interface (SEI) film. The destruction of the SEI film will lead to the continuous reaction between the electrode and the electrolyte, thereby consuming the limited lithium ion resources in the battery and causing the electrolyte to decompose. This not only leads to a decrease in battery capacity, but also increases the internal resistance of the battery, further affecting the battery's charging and discharging performance and efficiency.
[0005] In view of this, it is indeed necessary to provide a technical solution to the above problems. Summary of the invention
[0006] One of the purposes of the present invention is to provide a lithium ion battery to address the deficiencies of the prior art and solve the problems of poor positive electrode interface stability, poor SEI film stability and high negative electrode impedance in current lithium ion batteries under low temperature conditions.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] A lithium-ion battery, comprising a positive electrode sheet and an electrolyte, wherein the positive electrode material of the positive electrode sheet comprises a core body and a surface layer located on the surface of the core body; wherein the core body comprises a chemical formula of Lia MO b The main material is a main material, a ranges from 1 to 3, b ranges from 1 to 3, M is at least one of the transition metal ions, and the valence state of the M ion is +X; the surface layer contains A ions, and the valence state of the A ions is +Y; the core contains B ions, and the valence state of the B ions is +Z; wherein A and B are at least one of the main group or subgroup elements of IA to IVA; and X, Y, and Z satisfy the relationship: 1<Z<X≤Y.
[0009] The electrolyte includes BF 3 and Li q P r O s F t , wherein q+3r-2s-t=0 or q+5r-2s-t=0; the Li q P r O s F t The ratio of the total weight of the electrolyte is F%, 0.1≤F≤1, and the BF 3 The ratio of the total weight of the electrolyte is E%, 0.1≤E≤1, and E and F satisfy the relationship: F≤E≤4F.
[0010] The present invention uses Li a MO b As the main material, by controlling the radial distribution of AB ions with different valences in the positive electrode material, an NP structure similar to a semiconductor diode is formed. The surface layer of the positive electrode material contains high-valence A ions, and the inner layer contains low-valence B ions. By utilizing the characteristics of greater repulsion of A ions and less repulsion of B ions, the positive electrode material particles form a structure with greater resistance to lithium ion transmission on the surface and less resistance to lithium ion transmission in the inner layer. In this way, when charging, lithium ions escape from the inside of the positive electrode material particles to the outside, and need to move from the inner layer with less repulsion to the surface layer with greater repulsion. They will encounter corresponding resistance, which can reduce the upper limit of the outward transmission speed of lithium ions, thereby reducing the risk of lithium plating at the negative electrode. During low-temperature discharge, lithium ions are embedded inward from the surface of the positive electrode material particles, and need to move from the surface layer with greater repulsion to the inner layer with less repulsion. Their transmission speed can be improved, thereby improving the low-temperature discharge capacity of the battery. At the same time, with the improved electrolyte containing Li q P r O s F t and BF 3 , compound Li q P r O s F t A low-impedance SEI is formed on the negative electrode surface, but its dissociation ability is poor, and the amount of low-impedance SEI formed is small. 3It can form a complex with it to improve its dissociation ability, further reduce the negative electrode impedance, and then further improve the low-temperature discharge capability through the positive and negative electrodes.
[0011] Preferably, based on the mass of the main material, the mass content of the M ions is ≥ 10%.
[0012] Preferably, the weight proportion of the A ions in the surface layer is ≥200ppm; and / or, the interval extending 1μm from the surface of the core body toward its center is defined as the inner layer, and the weight proportion of the B ions in the inner layer is ≥200ppm. If the content of A ions in the surface layer is too low, the effect of reducing the lithium ion transmission speed cannot be achieved. Similarly, if the content of B ions in the core body is too low, the effect of increasing the lithium ion transmission speed cannot be achieved. By adopting the content parameters defined above in the present invention, the technical effect of simultaneously improving the electrode lithium precipitation and low-temperature discharge capacity can be achieved.
[0013] On the surface of the positive electrode material, the valence state of the A ion needs to be ≥ that of the M ion to achieve the effect of reducing the lithium ion transmission speed, and the effect is more obvious when the weight ratio of the A ion in the surface layer is ≥200ppm, and there is no effect when the content is lower. Inside the positive electrode, the valence state of the B ion needs to be ≤ that of the M ion to achieve the effect of promoting the lithium ion transmission speed, and the effect is more obvious when the weight ratio of the B ion in the inner layer is ≥200ppm. Lithium ions are inhibited by A ions when they are transmitted to the surface, and promoted by B ions when they are transmitted to the interior. The simultaneous presence of the two ions can achieve the effect of regulating the lithium ion extraction and embedding speed, thereby improving the room temperature high-rate charging performance and low-temperature discharge capacity of lithium batteries.
[0014] In some embodiments, the surface layer may also contain B ions appropriately, but in order to ensure that the surface layer inhibits the lithium ion transmission rate, the content of B ions needs to be controlled. Based on the weight ratio of A ions in the surface layer being ≥200ppm, the weight ratio of B ions in the surface layer needs to be controlled at 0-100ppm. If it exceeds this range, it will seriously affect the lithium ion transmission inhibition effect of the surface layer. Similarly, the core body may also contain A ions appropriately, but in order to ensure that the core body enhances the lithium ion transmission rate, the content of A ions needs to be controlled. Based on the weight ratio of B ions in the inner layer being ≥200ppm, the weight ratio of A ions in the inner layer needs to be controlled at 0-100ppm. If it exceeds this range, it will seriously affect the lithium ion transmission promotion effect of the core body.
[0015] The method for preparing the positive electrode material comprises the following steps:
[0016] S1, mixing the main material preparation raw materials including the lithium source and the M element precursor, and then dispersing them in an organic solvent, adding the B element precursor for premixing, and vacuum drying the mixture;
[0017] S2, dividing the mixture in step S1 into two groups, a and b, and then sintering them respectively to obtain product a and product b;
[0018] S3, crushing the product a and the product b prepared in S2 respectively to obtain large particles of product a and small particles of product b;
[0019] S4, mixing the large particles and the small particles obtained in S3 in a mass ratio of (7-9):(1-3), adding the A element precursor, and stirring and mixing;
[0020] S5. The mixture obtained in S4 is subjected to secondary sintering, crushing, and cooling to obtain the positive electrode material.
[0021] Preferably, in step S1, the premixing speed is 200-400 r / min, and the premixing time is 4-8 h; the vacuum drying temperature is 60-100° C., and the drying time is 10-15 h.
[0022] Preferably, in step S2, the primary sintering temperature is 800-1200°C, the primary sintering of the mixture of group a adopts a two-stage sintering method and the sintering time is 12-14 hours, and the primary sintering time of the mixture of group b is 5.5-7.5 hours.
[0023] Preferably, the two-stage sintering method includes: first continuously heating the temperature to D1°C at a heating rate of V1°C / min, then sintering at D1°C±50°C for t1 time, then continuously heating the temperature to D2°C at a heating rate of V2°C / min, then sintering at D2°C±50°C for t2 time, and finally annealing at a cooling rate of V3°C / min, wherein V1>V2, V2=V3, D1<D2, and t1=t2.
[0024] Preferably, the stirring and mixing speed in step S4 is 1000-1400 rpm, and the stirring time is 5-8 hours.
[0025] Preferably, in step S3, the crushed product a is large particles of 5 to 50 μm, and the crushed product b is small particles of 0.5 to 10 μm.
[0026] Preferably, in step S5, the secondary sintering temperature is 600-800° C., and the sintering time is 8-12 hours.
[0027] A second object of the present invention is to provide an electrical appliance comprising the lithium-ion battery described above.
[0028] Compared with the prior art, the beneficial effects of the present invention are as follows: the lithium-ion battery provided by the present invention has significant advantages in improving safety performance and charging efficiency by adjusting the electrolyte components and using a positive electrode sheet in combination. The positive electrode material in the positive electrode sheet adopts radially distributed AB ions with different valences to form an NP structure similar to a semiconductor diode, which has better structural stability, thermal stability and electrochemical performance. The surface layer of the positive electrode material can effectively reduce the thermal expansion caused by temperature changes during the lithium extraction process of the positive electrode material, and effectively improve the interfacial stability of the positive electrode material, while also having a good mitigating effect on the decomposition of the electrolyte and the corrosion of the positive electrode material; and the electrolyte used in combination contains Li q P r O s F and BF 3 , compound Li q P r O s F t A low-impedance SEI is formed on the negative electrode surface, but its dissociation ability is poor, and the amount of low-impedance SEI formed is small. 3 It can form a complex with it to improve its dissociation ability, further reduce the negative electrode impedance, and then further improve the low-temperature discharge capability through the positive and negative electrodes. DETAILED DESCRIPTION
[0029] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be further described in detail below in conjunction with specific implementation methods, but the implementation methods of the present invention are not limited thereto.
[0030] The terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0031] The present invention aims to provide a lithium ion battery, a lithium ion battery comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode material of the positive electrode sheet comprises a core body and a surface layer located on the surface of the core body; wherein the core body comprises a chemical formula of Li a MO bThe main material is a main material, a ranges from 1 to 3, b ranges from 1 to 3, M is at least one of the transition metal ions, and the valence state of the M ion is +X; the surface layer contains A ions, and the valence state of the A ions is +Y; the core contains B ions, and the valence state of the B ions is +Z; wherein A and B are at least one of the main group or subgroup elements of IA to IVA; and X, Y, and Z satisfy the relationship: 1<Z<X≤Y.
[0032] The electrolyte includes BF 3 and Li q P r O s F t , wherein q+3r-2s-t=0 or q+5r-2s-t=0; the Li q P r O s F t The ratio of the total weight of the electrolyte is F%, 0.1≤F≤1, and the BF 3 The ratio of the total weight of the electrolyte is E%, 0.1≤E≤1, and E and F satisfy the relationship: F≤E≤4F.
[0033] Among them, the specific value of the above a can be 1, 1.5, 2, 2.5, 3, and may include but are not limited to the values listed above; the specific value of the above b can be 1, 1.5, 2, 2.5, 3, and may include but are not limited to the values listed above.
[0034] The inventors discovered that IA~IVA main group or subgroup element ions with different positive valence states have an electrostatic repulsive effect on lithium ions, and the higher the valence state, the greater the electrostatic repulsion. The outer layer contains high-valence A ions with greater repulsion, while the inner layer contains low-valence B ions with less repulsion, forming a structure in which the surface layer lithium ion transmission resistance is large and the inner layer lithium ion transmission resistance is small inside the positive electrode material particles. In this way, when charging, lithium ions escape from the inside of the positive electrode material particles to the outside, and need to move from the inner layer with less repulsion to the surface layer with greater repulsion. They will encounter corresponding resistance, which can reduce the upper limit of the outward transmission speed of lithium ions, thereby reducing the risk of lithium plating at the negative electrode. During low-temperature discharge, lithium ions are embedded inward from the surface of the positive electrode material particles, and need to move from the surface layer with greater repulsion to the inner layer with less repulsion. Their transmission speed can be improved, thereby improving the low-temperature discharge capacity of the battery. The compound Li q P r O s F t A low-impedance SEI is formed on the negative electrode surface, but its dissociation ability is poor, and the amount of low-impedance SEI formed is small. 3It can form a complex with it to improve its dissociation ability, further reduce the negative electrode impedance, and then further improve the low-temperature discharge capability through the positive and negative electrodes.
[0035] In some embodiments, the method for preparing the positive electrode active material comprises the following steps:
[0036] S1, mixing the main material preparation raw materials including the lithium source and the M element precursor, and then dispersing them in an organic solvent, adding the B element precursor for premixing, and vacuum drying the mixture;
[0037] S2, dividing the mixture in step S1 into two groups, a and b, and then sintering them respectively to obtain product a and product b;
[0038] S3, crushing the product a and the product b prepared in S2 respectively to obtain large particles of product a and small particles of product b;
[0039] S4, mixing the large particles and the small particles obtained in S3 in a mass ratio of (7-9):(1-3), adding the A element precursor, and stirring and mixing;
[0040] S5. The mixture obtained in S4 is subjected to secondary sintering, crushing, and cooling to obtain the positive electrode material.
[0041] The positive electrode material prepared by the preparation method of the present invention has better structural stability, thermal stability and electrochemical performance. Among them, the coating material can effectively reduce the thermal expansion caused by the temperature increase during the lithium insertion and extraction process of the positive electrode material, and effectively reduce the mechanical attenuation of the coating layer, improve the interface stability of the positive electrode material, and at the same time play a good role in alleviating the decomposition of the electrolyte and the corrosion of the positive electrode material, so that the electrochemical performance of the positive electrode material under high voltage is improved.
[0042] In some embodiments, in step S1, the speed of the premix is 200-400 r / min, specifically 200 r / min, 210 r / min, 220 r / min, 230 r / min, 240 r / min, 250 r / min, 260 r / min, 270 r / min, 280 r / min, 290 r / min, 300 r / min, 310 r / min, 320 r / min, 330 r / min, 340 r / min, 350 r / min, 360 r / min, 370 r / min, 380 r / min min, 400r / min may include but are not limited to the values listed above; the premixing time is 4-8h, specifically 4h, 5h, 6h, 7h, 8h, and may include but are not limited to the values listed above; the vacuum drying temperature is 60-100℃, specifically 60℃, 65℃, 70℃, 75℃, 80℃, 85℃, 90℃, 95℃, 100℃, and may include but are not limited to the values listed above; the drying time is 10-15h, specifically 10h, 11h, 12h, 13h, 14h, 15h, and may include but are not limited to the values listed above.
[0043] In some embodiments, in step S2, the primary sintering temperature is 800-1200°C, and specifically can be 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, and can include but are not limited to the values listed above. The primary sintering of the mixture of group a adopts a two-stage sintering method and the sintering time is 12-14h, and the primary sintering time of the mixture of group b is 5.5-7.5h.
[0044] Among them, the two-stage sintering method includes: first continuously heating the temperature to D1℃ at a heating rate of V1℃ / min, then sintering at D1℃±50℃ for t1 time, then continuously heating the temperature to D2℃ at a heating rate of V2℃ / min, then sintering at D2℃±50℃ for t2 time, and finally annealing at a cooling rate of V3℃ / min, wherein V1>V2, V2=V3, D1<D2, t1=t2.
[0045] In some embodiments, the stirring and mixing speed in step S4 is 1000-1400 rpm, specifically 1000 rpm, 1050 rpm, 1100 rpm, 1150 rpm, 1200 rpm, 1250 rpm, 1300 rpm, 1350 rpm, 1400 rpm, 1450 rpm, 1500 rpm, and may include but are not limited to the values listed above; the stirring time is 5-8 h.
[0046] In some embodiments, in step S5, the secondary sintering temperature is 600-800°C, specifically 600°C, 650°C, 700°C, 750°C, 800°C, and may include but are not limited to the values listed above; the sintering time is 8-12h, specifically 8h, 9h, 10h, 11h, 12h, and may include but are not limited to the values listed above.
[0047] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be further described in detail below in conjunction with specific embodiments, but the embodiments of the present invention are not limited thereto.
[0048] Example 1
[0049] The preparation method of the positive electrode material is:
[0050] 1) Primary mixing: Li 2 CO 3 、Co 3 O 4 According to the Li:Co element stoichiometric ratio of 1.05:0.993, in order to compensate for the loss of lithium under high temperature sintering, the lithium source is measured at an excess of 5%, isopropanol is used as a dispersant, and the B element precursor is added. The solid and liquid mixtures are premixed in an oblique mixer, the premixing mechanical speed is 300r / min, and the mixing time is 6h. After premixing, the above materials are vacuum dried at 80°C overnight for 12h to volatilize the dispersant and water.
[0051] 2) Primary sintering: The premixed mixture is divided into two groups, a and b, and then transferred to a muffle furnace for sintering at 800-1200°C. Specifically, the mixture of group a is sintered in two stages: the temperature is continuously increased at a heating rate of 3°C / min for the first 3 hours, and then maintained at a temperature platform of 500-600°C for 2 hours. From the 5th to the 11th hour, the temperature is continuously increased at a heating rate of 1.5°C / min, and then maintained at a temperature platform of 1050±30°C for 2 hours. Finally, annealing is performed at a cooling rate of 1.5°C / min to obtain product a after primary sintering. The mixture of group b is sintered at 1000°C for 6 hours to obtain product b after primary sintering.
[0052] 3) Primary crushing: crush product a with a crusher at a medium crushing degree for 2 hours to obtain large particles; crush product b with a crusher at a medium crushing degree for 4 hours to obtain small particles.
[0053] 4) Secondary compounding: Mix large particles and small particles in a mass ratio of 8:2, add element A precursor, 500ppm Al 2 O 3and 800ppm LiF (LiF acts as a coating flux), the mixture is transferred to a high-speed stirrer, the stirring speed is 1000-1400r / min, and stirred for 6h.
[0054] 5) Secondary sintering: The mixture was transferred to a muffle furnace again, and the heating rate was set to 5°C / min until the temperature reached 750±30°C, and sintered for 10 hours, and then cooled at a cooling rate of 3°C / min until it cooled to room temperature to obtain a secondary sintered product.
[0055] 6) Secondary crushing: The secondary sintered product is crushed with a crusher, the crushing degree is selected to be medium, and the time is 4 hours to obtain the positive electrode material.
[0056] In this embodiment, the B element precursor is MgF 2 , A element precursor is TiO 2 .
[0057] Preparation of electrolyte: In a glove box filled with argon, the moisture content is less than 5ppm, the oxygen content is less than 5ppm, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DMC), ethyl propionate (EP), and propyl propionate (PP) are mixed according to the mass ratio of EC: PC: DMC: EP: PP = 1: 1: 2: 2: 2 to obtain an organic solvent; and 13.7wt% of lithium hexafluorophosphate, 1wt% of 1,3-propane sultone and 5wt% of fluoroethylene carbonate are added, and then 0.25wt% of BF 3 and 0.25wt%LiPO 2 F 2 Mix well to obtain an electrolyte.
[0058] Embodiment 2-6
[0059] The difference between Example 2-6 and Example 1 is that the electrolyte contains LiPO 2 F 2 and BF 3 The added amounts are different, see Table 3 for details.
[0060] The rest is the same as that of Example 1 and will not be described in detail.
[0061] Comparative Examples 1-6
[0062] The difference between Comparative Examples 1-6 and Example 1 is that BF is not added. 3 , while LiPO 2 F 2 The amount of addition is shown in Table 3.
[0063] The rest is the same as that of Example 1 and will not be described in detail.
[0064] Comparative Examples 7-11
[0065] The difference between Comparative Examples 7-11 and Example 1 is that LiPO is not added. 2 F 2 , and BF 3 The amount of addition is shown in Table 3.
[0066] The rest is the same as that of Example 1 and will not be described in detail.
[0067] Comparative Examples 12-17
[0068] The difference between Comparative Examples 12-17 and Example 1 is that the electrolyte contains LiPO 2 F 2 and BF 3 The added amounts are different, see Table 3 for details.
[0069] The rest is the same as that of Example 1 and will not be described in detail.
[0070] Comparative Examples 18-23
[0071] The difference between Comparative Examples 18-23 and Example 1 is that the electrolyte contains LiPO 2 F 2 and BF 3 The addition amount is different, and the element parameters contained in the electrode are different. The specific amount of electrolyte addition is shown in Table 3, and the specific electrode parameters are shown in Table 1.
[0072] The rest is the same as that of Example 1 and will not be described in detail.
[0073] The positive electrode sheets and electrolyte formulations of the above-mentioned Examples 1 to 6 and Comparative Examples 1 to 23 were sorted out as shown in Tables 1 to 3.
[0074] Table 1
[0075]
[0076] In Table 1, “ / ” represents that no relevant element is added.
[0077] Pole piece A: No A or B element precursors are added during the preparation of the positive electrode material.
[0078] Pole piece B: No B element precursor is added to the primary mixing material during the preparation process of the positive electrode material.
[0079] Pole piece C: No A element precursor is added to the secondary mixing material during the preparation of the positive electrode material.
[0080] Pole D: Add B element precursor MgF into the primary mixing material during the preparation of the positive electrode material. 2 , add A element precursor TiO 2 .
[0081] Pole E: Add TiO to the primary compound of the positive electrode material 2 MgF is added to the secondary compound 2 .
[0082] Pole piece F: A and B element precursors are added simultaneously to the primary mixture for preparing the positive electrode material, and A and B element precursors are not added to the secondary mixture.
[0083] Pole piece G: In the primary mixture for preparing the positive electrode material, no A and B element precursors are added, and A and B element precursors are added simultaneously in the secondary mixture.
[0084] After the prepared lithium-ion battery was dismantled and cleaned, the positive electrode was cut using CP, and the cross-section was tested using SEM-EDS to test the content of A and B elements on the surface and inside, respectively. The B element ratio was the weight ratio of B ions in the inner layer, and the inner layer was defined as above. The A element ratio was the weight ratio of A ions in the surface layer.
[0085] The results are shown in Table 2:
[0086] Table 2
[0087]
[0088] The collocation of the positive electrode and the electrolyte of the related embodiment is shown in Table 3 below, wherein BF 3 and LiPO 2 F 2 The content is calculated based on the total mass of the electrolyte.
[0089] Table 3
[0090]
[0091]
[0092]
[0093] The electrical properties of the above-mentioned Examples 1 to 6 and Comparative Examples 1 to 23 were tested, and the test results are shown in Table 4 below.
[0094] 1. Test of low temperature discharge capacity of lithium-ion battery: Place lithium-ion batteries in a 25℃ constant temperature chamber and let them stand for 30 minutes to allow the lithium-ion batteries to reach a constant temperature. Charge the lithium-ion battery that has reached a constant temperature at a constant current of 0.5C to a voltage of 4.48V, then charge it at a constant voltage of 4.48V to a current of 0.05C, let it stand for 10 minutes, and then discharge it at a constant current of 0.2C to a voltage of 3.0V, and record the initial discharge capacity; then charge the lithium-ion battery at a constant current of 0.5C to a voltage of 4.48V, then charge it at a constant voltage of 4.48V to a current of 0.05C, then set the temperature of the chamber to -20℃, let it stand for 120 minutes after reaching the temperature, and then discharge it at a constant current of 0.2C to a voltage of 3.0V, and record the low temperature discharge capacity. Calculate the low temperature discharge capacity ratio = low temperature discharge capacity / initial discharge capacity.
[0095] 2. Lithium deposition test: Charge the lithium-ion battery to 4.48V at XXC constant current, then charge at constant voltage to 0.05C until fully charged, then discharge at 0.7C constant current to 3.0V, this is one charge and discharge cycle. Repeat the charge and discharge for 20 cycles, charge at XXC constant current to 4.48V, then charge at constant voltage to 0.05C until fully charged, transfer the battery to the glove box for disassembly, separate the negative electrode sheet, and observe whether there is lithium dendrite formation on its surface.
[0096] Table 4
[0097]
[0098]
[0099] Results analysis: It can be seen from Examples 1-6 and Comparative Examples 1-23 that LiPO is added to the electrolyte at a specific ratio. 2 F 2 and BF 3 When used with positive electrode D, it can effectively improve the discharge capacity ratio in a low temperature environment of -10°C. The electrolyte contains Li q P r O s F and BF 3 , compound Li q P r O s F t A low-resistance SEI is formed on the negative electrode surface, and BF 3 It can form a complex with it, improve its dissociation ability, and further reduce the negative electrode impedance; at the same time, the B ion (Mg 2+ ) and A ions (Ti 4+ ) are respectively distributed in the inner layer and surface layer of the positive electrode material, the battery has a higher low-temperature discharge capacity and high-rate charging performance at room temperature.
[0100] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.
Claims
1. A lithium ion battery, comprising a positive electrode and an electrolyte, characterized in that: The positive electrode material of the positive electrode sheet includes a core body and a surface layer located on the surface of the core body; wherein the core body includes a chemical formula of Li a MO b The main material is a, a has a value range of 1 to 3, b has a value range of 1 to 3, M is at least one of transition metal ions, and the valence state of the M ion is +X; the surface layer contains A ions, and the valence state of the A ions is +Y; the core contains B ions, and the valence state of the B ions is +Z; wherein both A and B are at least one of the main group or subgroup elements of IA to IVA; and X, Y, and Z satisfy the relationship: 1<Z<X≤Y; The electrolyte includes BF3 and Li q P r O s F t , wherein q+3r-2s-t=0 or q+5r-2s-t=0; the Li q P r O s F t The ratio of the total weight of the electrolyte is F%, 0.1≤F≤1, the ratio of BF3 to the total weight of the electrolyte is E%, 0.1≤E≤1, and E and F satisfy the relationship: F≤E≤4F.
2. The lithium-ion battery according to claim 1, characterized in that Based on the mass of the main material, the mass content of the M ions is ≥10%.
3. The lithium-ion battery according to claim 1, characterized in that The weight proportion of the A ions in the surface layer is ≥200ppm; and / or, the interval extending 1μm from the surface of the core body toward its center is defined as the inner layer, and the weight proportion of the B ions in the inner layer is ≥200ppm.
4. The lithium-ion battery according to claim 1, characterized in that: The weight proportion of B ions in the surface layer is 0 to 100 ppm; and / or the weight proportion of A ions in the inner layer is 0 to 100 ppm.
5. The lithium ion battery according to any one of claims 1 to 4, characterized in that: The method for preparing the positive electrode active material comprises the following steps: S1, mixing the main material preparation raw materials including the lithium source and the M element precursor, then dispersing them in an organic solvent, adding the B element precursor for premixing, and vacuum drying the mixture; S2, dividing the mixture in step S1 into two groups, a and b, and then sintering them respectively to obtain product a and product b; S3, crushing the product a and the product b prepared in S2 respectively to obtain large particles of product a and small particles of product b; S4, mixing the large particles and small particles obtained in S3 in a mass ratio of (7-9):(1-3), adding the A element precursor, and stirring and mixing; S5. The mixture obtained in S4 is subjected to secondary sintering, crushing, and cooling to obtain the positive electrode material.
6. The lithium-ion battery according to claim 5, characterized in that: In step S1, the premixing speed is 200-400 r / min, and the premixing time is 4-8 hours; the vacuum drying temperature is 60-100° C., and the drying time is 10-15 hours.
7. The lithium-ion battery according to claim 5, characterized in that In step S2, the primary sintering temperature is 800-1200°C, the primary sintering of the mixture of group a adopts a two-stage sintering method and the sintering time is 12-14 hours, and the primary sintering time of the mixture of group b is 5.5-7.5 hours; Preferably, the two-stage sintering method includes: first continuously heating the temperature to D1°C at a heating rate of V1°C / min, then sintering at D1°C±50°C for t1 time, then continuously heating the temperature to D2°C at a heating rate of V2°C / min, then sintering at D2°C±50°C for t2 time, and finally annealing at a cooling rate of V3°C / min, wherein V1>V2, V2=V3, D1<D2, and t1=t2.
8. The lithium-ion battery according to claim 5, characterized in that: In step S3, the crushed product a is large particles of 5 to 50 μm, and the crushed product b is small particles of 0.5 to 10 μm.
9. The lithium-ion battery according to claim 5, characterized in that: In step S5, the secondary sintering temperature is 600-800° C., and the sintering time is 8-12 hours.
10. An electrical appliance, characterized in that: A lithium ion battery comprising any one of claims 1 to 4.
Citation Information
Patent Citations
Method for preparing graphene by continuous peeling on basis of electrostatic repulsive force
CN107032339A
Electrolyte for inhibiting lithium dendrites and preparation method thereof, and lithium battery
CN107275671A
Low temperature lithium ion battery
CN107482253A
Lithium ion battery electrolyte and lithium ion battery containing same
CN113140796A
Preparation method of lithium difluorophosphate
CN114560456A